Antibody Correlates of Protection From Severe Respiratory Syncytial Virus Disease in a Vaccine Efficacy Trial. (12th January 2023) - Fong, Youyi; Huang, Ying; Borate, Bhavesh; van der Laan, Lars W P; Zhang, Wenbo; Carpp, Lindsay N; Cho, Iksung; Glenn, Greg; Fries, Louis; Gottardo, Raphael; Gilbert, Peter B
Abstract: Background: Respiratory syncytial virus (RSV) can cause serious lung infections in young children and there is currently no available vaccine. Methods: We used complementary statistical frameworks to analyze 4 RSV serology measurements in mothers and their infants in South Africa who participated in a phase 3 maternal immunization trial of an RSV F protein nanoparticle vaccine as correlates of risk and of protection against different RSV disease endpoints. Results: We found evidence to support each antibody measurement—encompassing RSV-neutralizing antibodies and F surface glycoprotein-binding antibodies—as an inverse correlate of risk of RSV-associated acute lower respiratory tract infection with severe hypoxia in at least 1 framework, with vaccine-induced fold-rise from the maternal enrollment to day 14 samples of anti-F immunoglobulin G (IgG) binding antibodies having the most consistent evidence. This evidence includes a significant association of fold-rise anti-F IgG with vaccine efficacy (VE); achieving a baseline covariate-adjusted VE of 75% requires a vaccine-induced maternal anti-F IgG fold-rise of around 16. Neither multivariable logistic regression nor superlearning analyses showed benefit to including multiple time points or assays in the same model, suggesting a parsimonious correlate. Post hoc exploratory analyses supported adherence of vaccine-induced maternal anti-F IgG fold-rise to the Prentice criteria for a valid surrogate endpoint. Conclusions: Our results suggest that the vaccine induced protective anti-F antibody responses. If this finding is confirmed, VE could potentially be augmented by increasing these responses.